Pelatihan Perancangan Semprotan Hama Elektrik Sederhana Kepada Masyarakat Pertanian Desa Lok Baintan Luar - Irfan Rusydi Triyanto; Yusri; Khairul Sadri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This service aims to enhance the understanding and use of simple technologies by the villagers of Lok Baintan Luar, especially in the design of simple electric sprayers. The implementation approach adopted included a series of workshops and training aimed at the farming community of Lok Baintan Luar village. This dedication has created a significant positive impact. First, there is an increase in the agricultural community's enthusiasm for learning this simple technology. Workshop and training participants were actively engaged in the learning process, showing a keen interest in learning, and implementing this simple electrospray technology in their agricultural practices. Second, this commitment also creates strong momentum within the agricultural community to adopt this simple technology into their daily operations. This reflects their deep desire to increase farm efficiency and productivity using accessible technology. As a result, this service not only succeeds in increasing people's understanding of a simple technology but also encourages them to adopt this technology as a valuable tool in their agricultural practices, has a positive impact on local agricultural development.